Correlation of PD-L1 expression on tumor cell and tumor infiltrating immune cell with 18F-fluorodeoxyglucose uptake on PET/computed tomography in surgically resected pulmonary adenocarcinoma. Issue 3 (March 2020) - Hu, Bingxin; Xiao, Jie; Xiu, Yan; Fu, Zhequan; Shi, Hongcheng; Cheng, Dengfeng
Abstract : Objective: The uptake of 18 F-fluorodeoxyglucose ( 18 F-FDG) PET/computed tomography (CT) is known to be linked to programmed death ligand 1 (PD-L1) expression on tumor cells (TC). However, the association between PD-L1 expression on immune cells (IC) and 18 F-FDG accumulation is still unclear. Here, we conducted a clinicopathological study to investigate the relationship between PD-L1 expression on TC/IC and 18 F-FDG uptake in patients with surgically resected pulmonary adenocarcinoma (ADC). Methods: A total of 450 ADC patients who underwent preoperative 18 F-FDG-PET/CT imaging were analyzed retrospectively. Immunohistochemistry analysis was performed for PD-L1 expression on TC and IC in ADC specimens with SP142. PD-L1 expression was performed on whole-tissue sections and given scores (0/1/2/3) according to percent of PD-L1 + cells in TC and IC. Results: Compared to TC0 and IC0, PD-L1 positive expression was 90.4% (407/450) in ADC specimens. Both PD-L1 expression score on TC and IC were associated with maximum standardized uptake (SUVmax). SUVmax augmented with increasing PD-L1 expression (TC0 and IC0, 4.3 ± 3.4; TC or IC1/2/3, 7.7 ± 5.6; TC or IC2/3, 8.1 ± 5.6; TC or IC3, 8.4 ± 5.4). The best cut-off value of PD-L1 expression, determined by receiver operating characteristic curve, was 5.1 for TC or IC1/2/3 [area under the curve (AUC) = 0.713, sensitivity 62.2%, specificity 72.1%]. Multivariate analysis demonstrated that TC or IC1/2/3 subset was correlated with histological subtype, PD-1 expression on IC and SUVmax. Conclusion: High SUVmax is associated with PD-L1 expression on TC and IC in surgically resected pulmonary ADC. 18 F-FDG-PET/CT imaging can be a potential tool to evaluate PD-L1 expression in pulmonary ADC. Abstract : Supplemental Digital Content is available in the text.